2012
DOI: 10.1038/eye.2012.106
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 dose-escalation study of a siRNA targeting the RTP801 gene in age-related macular degeneration patients

Abstract: Background To evaluate the safety, tolerability, pharmacokinetics, and dose-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 14 publications
(13 reference statements)
1
36
0
Order By: Relevance
“…78 Clinical trials of intravitreal siRNA treatments, including those targeting RTP801, have reported safety and efficacy for ocular diseases. 48,50,86 Despite the inherent vulnerabilities of immunofluorescence-based analyses, such as antibody specificity and limitations of sampling for neuronal/glial quantification, both our in vivo and in vitro observations yielded consistent results. Here, we show that siRNA-mediated knockdown of RTP801 promotes RGC neuroprotection, supports elongation of regenerating axons after ONC in vivo, and potentiates a proregenerative reactive glial response to injury.…”
Section: Discussionsupporting
confidence: 65%
“…78 Clinical trials of intravitreal siRNA treatments, including those targeting RTP801, have reported safety and efficacy for ocular diseases. 48,50,86 Despite the inherent vulnerabilities of immunofluorescence-based analyses, such as antibody specificity and limitations of sampling for neuronal/glial quantification, both our in vivo and in vitro observations yielded consistent results. Here, we show that siRNA-mediated knockdown of RTP801 promotes RGC neuroprotection, supports elongation of regenerating axons after ONC in vivo, and potentiates a proregenerative reactive glial response to injury.…”
Section: Discussionsupporting
confidence: 65%
“…Successful knock-down of VEGF receptor-1 (VEGFR1) after injection of naked stabilitymodified VEGFR1 siRNA has been demonstrated in mouse models (Shen et al, 2006). This route of administration is also currently being used in clinical trials with siRNAs targeting VEGF (Brucker, 2006), VEGFR1 (Kaiser et al, 2010) and hypoxia-inducible RTP801 genes (Nguyen et al, 2012b). As chemically modified siRNAs can also be degraded by vitreous endonucleases (Beverly et al, 2006), siRNA-based treatments of posterior segment diseases could require multiple intravitreal injections, similar to conventional treatments.…”
Section: Figurementioning
confidence: 99%
“…In addition, this siRNA targeting RTP801 gene is currently in clinical trials for the treatment of wet AMD. A phase I trial testing the efficacy and safety of stable, modified PF-655 administered alone by intravitreal injection (Nguyen et al, 2012b), and a phase II study (MONET) comparing PF-655 efficacy with that of ranibizumab as well as a ranibizumab/PF-655 combination therapy versus ranibizumab monotherapy (Nguyen et al, 2012c) have recently been performed (Table 1). The best-corrected visual acuity in AMD patients treated with PF-655 alone was less than that in the ranibizumab group.…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%
“…It was well tolerated without any significant safety issue. However, the limited sample size was not sufficient to statistically evaluate efficacy [149].…”
Section: 6age-related Macular Degenerationmentioning
confidence: 99%